Nitrogen fertilization in serial cycles and its impact on yield and quality of peach - Brunetto, Gustavo; Melo, George Wellington de; Kaminski, João; Ceretta, Carlos Alberto (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this work was to evaluate the effect of N fertilization on N content of the leaf, shoot growth, yield and on physico-chemical quality of peach fruits. The experiment was carried out from 2000 to 2002, in an orchard of peach trees, cv. Chimarrita, grafted on Aldrighi rootstock, at Pinto Bandeira city, in Rio Grande do Sul State, Southern Brazil, in a Haplumbrept soil. The treatments were 0, 22, 44, 66, and 88 kg ha-1 N per year. In the growing seasons leaves were collected, oven-dried and analyzed for total N, and the length of selected shoots was determined after leaf abscission. Fruits were collected when ripen, for the determination of diameter, mass, yield, total N, total soluble solids, total titratable acidity and pulp firmness. Remaining fruits were cooled through forced-air system and kept in cold storage for seven days, then pulp firmness was determined. N fertilization in peach trees increases N content in the leaves and in the fruits. N fertilization do not affect the length of shoots, and the diameter, mass, total titratable acidity and pulp firmness of peach fruits.